1999
DOI: 10.1007/bf03184452
|View full text |Cite
|
Sign up to set email alerts
|

Tool trajectory generation based on tool deflection effects in flat-end milling process(I)

Abstract: The objective of this paper is to deal with the deflection effects of cutting tools. Deflection is an important factor in obtaining accurate surfaces in milling operations. We have tried to integrate tool deflection effects for tool path generation in flat-end milling without modifying the cutting conditions. To carry out our objective, a tool path compensation methodology is presented. The cutting forces are modeled on the specific cutting pressure K r and K», determined experimentally. The calculations of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Most of the studies estimated the surface error by treating the tool as a cantilever beam, assuming the cutting force to act at the centre of the axial depth of cut as a concentrated force. When the tool length is much longer than the axial depth of cut, the difference in estimating the surface error by treating the cutting force as a concentrated instead of distributed force is negligible [29]. The current authors define the surface error in the normal direction to the curved surface and the tool is assumed to be rigid in the axial direction compared with that in the normal and feed directions.…”
Section: Surface Error Modellingmentioning
confidence: 99%
“…Most of the studies estimated the surface error by treating the tool as a cantilever beam, assuming the cutting force to act at the centre of the axial depth of cut as a concentrated force. When the tool length is much longer than the axial depth of cut, the difference in estimating the surface error by treating the cutting force as a concentrated instead of distributed force is negligible [29]. The current authors define the surface error in the normal direction to the curved surface and the tool is assumed to be rigid in the axial direction compared with that in the normal and feed directions.…”
Section: Surface Error Modellingmentioning
confidence: 99%
“…These independent variables are closely related to the cutting force and the tool deflection. It has been also shown that such variables affect the end-milled surface integrity [8][9][10][11]. The previous research results by Kim [12,13] showed that geometrical surface error is caused by the surface generation mechanism of end milling itself.…”
Section: Introductionmentioning
confidence: 98%
“…Kline and Devor [17] investigated the influence of the static deflection of the end mill on the geometric error of a machined surface using a cantilever beam model. Seo and Cho [18,19] developed a mirror image method to compensate for the machining error caused by the cutter deflection, wherein the cutter deflection was predicted using a finite element simulation model. Rao and Rao [20] compensated for the NC tool path by estimating the cutting force and cutter deflection to improve the machining accuracy of a curved surface.…”
Section: Introductionmentioning
confidence: 99%